Experimental Research of the Influence of Immunomodulators on Efficiency Using of Brucellosis Living Dry Vaccine - N. V. Bogacheva; V. Y. Okhapkina; N. V. Pyatkova; A. K. Fedotov; A. S. Kucherenko (Эпидемиология и вакцинопрофилактика, 2016)
Brucellosis living dry vaccine, used for immunization of brucellosis, has a number of drawbacks. In this regard, the article discusses the using of immunomodulators for enhance of the effectiveness of immunization and reduce of the risk of side effects and complications. Likopid, polioksidony and timogen were used as immunomodulators. As a result of valuation cellular and humoral immunity of different laboratory animals and valuation of protective efficacy of brucellosis living vaccine, the presence of a complex stimulating effect on the efficiency of immunogenesis licopid was established.